Side‐to‐side supercharging nerve allograft enhances neurotrophic potential. Issue 2 (29th November 2019) - Isaacs, Jonathan; Feger, Mark A.; Mallu, Satya; Patel, Gaurangkumar; Debkowska, Monika; Yager, Dorne; Ernst, Brady; Chilukuri, Sravya; Moser, Matthew; Kurtz, Camden
Abstract: Introduction: Critical limitations of processed acellular nerve allograft (PNA) are linked to Schwann cell function. Side‐to‐side bridge grafting may enhance PNA neurotrophic potential. Methods: Sprague–Dawley rats underwent tibial nerve transection and immediate repair with 20‐mm PNA (n = 33) or isograft (ISO; n = 9) or 40‐mm PNA (n = 33) or ISO (n = 9). Processed acellular nerve allograft groups received zero, one, or three side‐to‐side bridge grafts between the peroneal nerve and graft. Muscle weight, force generation, and nerve histomorphology were tested 20 weeks after repair. Selected animals underwent neuron back labeling with fluorescent dyes. Results: Inner axon diameters, g‐ratios, and axon counts were smaller in the distal vs proximal aspect of each graft ( P < .05). Schwann cell counts were greater, with a lower proportion of senescent cells for groups with bridges ( P < .05). Retrograde labeling demonstrated that 6.6% to 17.7% of reinnervating neurons were from the peroneal pool. Discussion: Bridge grafting positively influenced muscle recovery and Schwann cell counts and senescence after long PNA nerve reconstruction.